Altered Resting State Functional Activity of Brain Regions in Neovascular Glaucoma: A Resting-State Functional Magnetic Resonance Imaging Study - Yu, Chao; Li, Chu-Qi; Ge, Qian-Min; Shu, Hui-Ye; Liao, Xu-Lin; Pan, Yi-Cong; Wu, Jie-Li; Su, Ting; Zhang, Li-Juan; Liang, Rong-Bin; Shao, Yi; Zeng, Er-Ming (Frontiers in Neuroscience, 2021)
Background As a severe ocular disease, neovascular glaucoma (NVG) leads to irreversible damage to the eye and causes anomalous activity in the cortical and pre-cortical visual system. However, currently there are few studies in this area. The present trial evaluated regional brain activity in NVG patients utilizing the percent amplitude of fluctuation (PerAF) approach. Methods Resting-state functional MRI (rs-fMRI) scans were conducted in 18 individuals with NVG and 18 healthy controls (HCs), matched for education level, gender, and age. The PerAF method was applied to assess brain activity. Mean PerAF values of brain regions in NVG and HCs were compared using receiver operating characteristic (ROC) curves. Results Lower PerAF values were found in the NVG group than in controls in the right anterior cingulate and paracingulate gyri (ACG.R), right superior occipital gyrus (SOG.R) and left superior frontal gyrus (orbital part) (ORBsup.L) (p<0.001). In contrast, PerAF value was higher in NVG patients than in controls in the left inferior temporal gyrus (ITG.L) (p<0.001). Conclusion Abnormal activity in several brain regions in NVG patients may reveal neuropathological mechanism of NVG and enhance understanding of this disease. Further research is needed to establish whether these changes in brain activity may be useful as diagnostic indicators.